Transformasi Manajemen Organisasi Melalui Integrasi Pengembangan SDM Dan Penilaian Kinerja Untuk Peningkatan Efektivitas Di SMP Islam Al-Ummah Jombang - Achmad Rosyady Arrif'an; Nurindah Putri Fatimiah; Mochammad Ichsan Baqi; Muchamad Yusuf; Mardiyah Mardiyah (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to describe the organizational management transformation through the integration of human resource development and performance assessment to enhance school effectiveness at SMP Islam Al-Ummah Jombang. Using a qualitative approach, data were collected through in-depth interviews, observations, and managerial document analysis. The findings reveal that the transformation occurred across four key dimensions: data-driven work systems, decentralized organizational structure, strengthened collaborative work culture, and management digitalization. The integration of HR development and performance assessment improved the accuracy of teacher coaching, enhanced academic supervision, and fostered a continuous reflective culture. The transformation positively impacted managerial effectiveness, instructional quality, and organizational cohesion. Despite these improvements, several challenges emerged, including uneven teacher data literacy, the need for stronger cross-unit coordination, and limited digital infrastructure. These findings highlight the importance of digital competence enhancement, coordinated SOPs, and adequate technological support to sustain school management transformation.